The Relationship of Work Stress and Workload to Work Fatigue in Nurses During The Covid-19 Pandemic - Lys Ceryah Hutasoit, Mey; Ma'arif, Sugeng (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2022)
The improvement of the quality of hospital services continues to be done by evaluate fatigue of nurse work. Nurse work fatigue is a complete criterion not only regarding fatigue that is physical and psychological only, but has more to do with a decrease in physical performance, feeling tired, decreased motivation, and decreased work productivity. One of the factors that affect nurse ape fatigue is workload and work stress. The method is qualitative, using design cross sectional study, carried out in February - March 2022. The sample in this study was 64 nurses, taken with the technique of total sampling. Using univariate, bivariate analysis (with Chi Square test). This study shows that most respondents at Bintaro IMC Hospital have heavy workload (67%), very heavy (33%) and work stress with heavy category (75%) and nurse fatigue in high category (36%), very high (23%), then there is a relationship of workload and stress of nurses to nurse work fatigue at IMC Bintaro Hospital (P Value = 0.000). Keywords: Workload, Work Stress, Work Fatigue